Pemetaan Dusun dan Jalan sebagai Upaya Pengembangan Informasi Wilayah Desa - Bungaran Sinaga; Fadil Fadil; Intan Dwi Wahyuni; Khairun Nisa; Muhammad Naufal Erian (Lembaga Pengembangan Kinerja Dosen, 2026)
Village regional information plays an important role in supporting community services and effective development planning. However, some rural areas still face limitations in information regarding hamlet boundaries and road access, including Lunto Barat Village, Lembah Segar District, Sawahlunto City. This Community Service Program (KKN) aimed to improve the availability and accessibility of village regional information through hamlet and road mapping activities. The methods applied included field observation, direct road data collection with village officials, preparation of hamlet maps, and environmental development activities through community-based planting. The results indicated that the mapping activities provided clearer information on hamlet boundaries and village road networks, thereby facilitating community access to regional information. Furthermore, the resulting village map helped both residents and visitors locate destinations more effectively. This program demonstrates that village mapping activities not only enhance access to regional information but also contribute to more structured and participatory village development.